FINANCIAL RATIO ANALYSIS TO MEASURE THE FINANCIAL PERFORMANCE OF THE REGIONAL GOVERNMENT OF GORONTALO DISTRICT FISCAL YEAR 2020-2023 - Heriyanto, Edwin; Daryatno, Andreas Bambang (International Journal of Application on Economics and Business, 2025)
This study aims to assess the financial performance of Gorontalo Regency in the last four years (2020-2023) through a financial ratio analysis approach including the regional financial efficiency ratio, the effectiveness ratio of regional original income, the ratio of regional financial independence, and the ratio of regional financial efficiency. This study is expected to be an effort to improve the Performance of the Gorontalo Regency Government by knowing the financial condition of the Gorontalo Regency Government. This study applies a quantitative descriptive approach that aims to describe in detail and facts, symptoms and phenomena of an event. Data collection uses secondary data, namely the Gorontalo Regency Government APBD Financial Realization Report. The results of this study show the performance of Gorontalo Regency, regional financial independence is at a very low level and is included in the category of instructive relationship patterns. Then according to the regional financial management efficiency ratio, the assessment is inefficient, then the regional original income effectiveness ratio shows ineffective results and performance based on the regional original income growth ratio has not shown positive developments.